Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.